Prosedur Penggunaan Alat Penghalus Gula Aren Semut Berdasarkan Standar Operasional Pengoperasian (Sop) - Parulian Pasaribu, Saut; Satria, Tan Rico; Maimuhalif, Lidjen; Nuradi, Nuradi (Jurnal Teknik Informatika dan Elektro, 2021)
This study aims to determine the procedure and how to operate the palm sugar grinding machine (disk mill) through standard operating procedures, this process goes through the milling and screening stages. This ant palm sugar grinding machine is equipped with a gasoline-powered motor with a power of 5.5 PK PRT or 2 HP which is connected by a V Belt to the driving motor which will automatically grind the ant palm sugar when the machine is turned on. This ant palm sugar grinding machine works to grind/refine the palm sugar in the form of powder/crystals to make it smooth.